2009
DOI: 10.1176/ps.2009.60.9.1245
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Falls Among Psychiatric Inpatients: A Case-Control Study at a State Psychiatric Facility

Abstract: Risk factors identified in this study should be assessed in replication studies. Psychiatric clinicians can use such risk factors to create evidence-based fall prevention programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 11 publications
2
27
0
Order By: Relevance
“…For clonazepam, the duration of past treatment was found to be a more important risk factor over the dose. Estrin et al (2009) suggested a fall prevention program at psychiatric hospitals to identify patients at high risk of falling. Our present work provided clear evidence for that the inter-individual variability in clonazepam metabolism can be estimated by the analysis of patients’ CYP3A4 expression.…”
Section: Discussionmentioning
confidence: 99%
“…For clonazepam, the duration of past treatment was found to be a more important risk factor over the dose. Estrin et al (2009) suggested a fall prevention program at psychiatric hospitals to identify patients at high risk of falling. Our present work provided clear evidence for that the inter-individual variability in clonazepam metabolism can be estimated by the analysis of patients’ CYP3A4 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Other than poor physical health (Estrin et al, 2009;Lord et al, 1991), depression (Gassmann et al, 2009;Launay et al, 2013;Tsai et al, 1998), and insomnia (Avidan et al, 2005;Mahgoub et al, 2012), most antidepressants, especially selective serotonin reuptake inhibitors, have long been recognized as a contributory factor to falls (Coupland et al, 2011;Darowski et al, 2009). The use of benzodiazepine or non-benzodiazepine sedative-hypnotics for severe insomnia would also further increase the risk of falling (Diem et al, 2014;Estrin et al, 2009;Obayashi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The use of benzodiazepine or non-benzodiazepine sedative-hypnotics for severe insomnia would also further increase the risk of falling (Diem et al, 2014;Estrin et al, 2009;Obayashi et al, 2013). A convergence of these factors would synergistically increase the risk of falls in patients with comorbid MDD and severe insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…Psychiatric illnesses could lead to perceptual changes and temporary impairment in their judgment and ability to recognize hazards. Patients who fell were commonly diagnosed with depression, 19,[22][23][24] bipolar disorder, [24][25][26] and dementia or Alzheimer's disease. 22,25,27 Neglect of one's safety and unawareness of surround- ing environment in patients with depression were also identified as contributing factors to falls.…”
Section: Risk Factorsmentioning
confidence: 99%